Electrochemical behavior of plutonium fluoride species in LiF-CaF2 eutectic melt. (1st April 2019) - Claquesin, Julien; Lemoine, Olivier; Gibilaro, Mathieu; Massot, Laurent; Chamelot, Pierre; Bourges, Gilles
Abstract: The electrochemical behavior of plutonium fluoride species was investigated in molten LiF-CaF2 medium in the 1093–1153 K temperature range with PuF4 additions. A preliminary thermodynamic study supposed a Pu(IV) carboreduction into Pu(III) and that Pu(III) reduction into metal proceeds in one step. Then, an electrochemical study was carried out on an inert electrode (tungsten) and confirmed the thermodynamic predictions: Pu(IV) is spontaneously reduced into Pu(III) in presence of carbon and Pu(III) is directly reduced into Pu(0): Pu(III) + 3e −  = Pu(0). Moreover, Pu(III) reduction mechanism is a diffusion controlled process. Diffusion coefficients were calculated at different temperatures and obey to an Arrhenius' type law with an activation energy of 63 ± 3 kJ mol −1 . The standard potential of Pu(III)/Pu(0) was determined at 1113 K and is found to be −4.61 V vs. F2 (gaz) /F − . This value permitted to calculate activity coefficients for several molalities.